Foetal growth restriction in mice modifies postnatal airway responsiveness in an age and sex-dependent manner - Wang, K.; Larcombe, Alexander; Berry, L.; Morton, J.; Davidge, S.; James, A.; Noble, P. (Portland Press Ltd., 2018)
Epidemiological studies demonstrate an association between intrauterine growth restriction (IUGR) and asthma; however the underlyingmechanism is unknown. We investigated the impact of maternal hypoxia-induced IUGR on airway responsiveness in male and female mice during juvenility and adulthood. Pregnant BALB/c mice were housed under hypoxic conditions for gestational days 11-17.5 and then returned to normoxic conditions for the remainder of pregnancy. A control group was housed under normoxic conditions throughout pregnancy. Offspring were studied at 2 weeks (juveniles) and 8 weeks (adults), where lung volume was assessed by plethysmography, airway responsiveness to methacholine determined by the forced oscillation technique and lungs fixed for morphometry. IUGR offspring were lighter at birth, exhibited "catch-up growth" by 2 weeks, but were again lighter in adulthood. IUGR males were "hyper-responsive" at 2 weeks and "hypo-responsive" as adults, in contrast with IUGR females who were hyper-responsive in adulthood. IUGR males had increased inner and total wall thickness at 2 weeks which resolved by adulthood, while airways in IUGR females were structurally normal throughout life. There were no differences in lung volume between Control and IUGR offspring at any age. Our data demonstrate changes in airway responsiveness as a result of IUGR that could influence susceptibility to asthma development and contribute to sexual dimorphism in asthma prevalence which switches from a male dominated disease in early life to a female dominated disease in adulthood.